Enabling development, manufacturing, and regulatory approval of biotherapeutics through advances in mass spectrometry. (October 2021) - Apostol, Izydor; Bondarenko, Pavel V; Ren, Da; Semin, David J; Wu, Chao-Hsiang; Zhang, Zhongqi; Goudar, Chetan T
Abstract : Rapid technological advances have significantly improved the capability, versatility, and robustness of mass spectrometers which has led to them playing a central role in the development, characterization, and regulatory filings of biopharmaceuticals. Their application spans the entire continuum of drug development, starting with discovery research through product development, characterization, and marketing authorization and continues well into product life cycle management. The scope of application extends beyond traditional protein characterization and includes elements like clone selection, cell culture physiology and bioprocess optimization, investigation support, and process analytical technology. More recently, advances in the MS-based multi-attribute method are enabling the introduction of MS in a cGMP environment for routine release and stability testing. While most applications of MS to date have been for monoclonal antibodies, the successes and learnings should translate to the characterization of next-gen biotherapeutics where modalities like multispecifics could be more prevalent. In this review, we describe the most significant advances in MS and correlate them to the broad spectrum of applications to biotherapeutic development. We anticipate rapid technological improvements to continue that will further accelerate widespread deployment of MS, thereby elevating our overall understanding of product quality and enabling attribute-focused product development.